The Daily Practice of Compassion : A History of the University of New Mexico School of Medicine, Its People, and Its Mission, 1964-2014 - Wang, Dora; Carter, Shannan L. (Book collections on Project MUSE., 2014)
Rich with anecdotes and personality, Dora Calott Wang's account is a must-read for anyone curious about health care in New Mexico.